2004
DOI: 10.1007/s00127-004-0758-0
|View full text |Cite
|
Sign up to set email alerts
|

Teachers? knowledge, beliefs and attitudes concerning schizophrenia

Abstract: Japanese and Taiwanese teachers' knowledge, beliefs and attitudes regarding schizophrenia were similar to those found in the general public in Western societies. Although the present study is limited in sampling and the components of the mental health literacy investigated, several working hypotheses have been extracted from it to be tested in future investigations on the Japanese and Taiwanese and other Asian general public's mental health literacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(91 citation statements)
references
References 21 publications
6
83
0
2
Order By: Relevance
“…The results of our study as well as past studies on patients with HIV suggest that interventions to increase knowledge level about an illness are important for the stigmatized people. In particular, people living in Japan are likely to lack knowledge about schizophrenia [6,20]; thus, early provision of correct information about schizophrenia for people with this disease is vital to prevent self-stigmatization. Two essential questions remain unanswered: What kind of knowledge should we provide and how should we share the information?…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study as well as past studies on patients with HIV suggest that interventions to increase knowledge level about an illness are important for the stigmatized people. In particular, people living in Japan are likely to lack knowledge about schizophrenia [6,20]; thus, early provision of correct information about schizophrenia for people with this disease is vital to prevent self-stigmatization. Two essential questions remain unanswered: What kind of knowledge should we provide and how should we share the information?…”
Section: Discussionmentioning
confidence: 99%
“…Mental illness is a serious burden for developed and non-developed countries [5,6]. Mental health problems are leading causes of the non-communicable burden, because of being accounted for 6.6% of global disability-adjusted life years and 18.9% of global years lived with disability [2].…”
Section: Introductionmentioning
confidence: 99%
“…Mental health literacy (MHL) has been defined as "knowledge and beliefs about mental disorders which aid their recognition, management, or prevention" [2,6,7]. The definition of MHL includes awareness and perception about mental illnesses, which support their recognition; the ability to identify specific disorders; knowing how to seek professional help; knowledge of risk factors and causes, and attitudes that promote identification [2,[7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…A cross-cultural and cross-national comparison of caregiver burden between Japan and Taiwan showed that Japanese respondents perceived a significantly stronger stigma for the parents and neighbors of a person with a mental illness presented in a vignette than did Taiwanese respondents (Shinfuku, 1998;Kurumatani et al, 2004). Haraguchi et al reported that knowledge of mental illness and medication were greater in Japan than in China, but social distance for persons with mental illness was greater in Japan than in China.…”
Section: Caregiver Burden and Cultural Comparisonmentioning
confidence: 99%
“…It has been reported that the strong stigma among Japanese respondents may be a consequence of the limited experience of the general public with psychiatric patients in the community. This limited experience could be attributed to Japan's institutionalization rate for schizophrenia patients, which is the highest in the world (Kurumatani et al, 2004).…”
Section: Public Endorsement Of Stigma Perceptionmentioning
confidence: 99%